2000
DOI: 10.1046/j.1523-1755.2000.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting clinical outcome in the elderly renal transplant recipient

Abstract: Renal transplantation is a safe and effective therapy for the older renal failure patient. In the absence of identified risk factors, graft survival is equivalent to that seen in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
56
4
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 13 publications
(7 reference statements)
12
56
4
3
Order By: Relevance
“…[3][4][5] Several studies have reported that graft and patient survivals were lower among patients 60 years or older, when compared with recipients aged 18 to 59. 6,7 On the other hand, similar results between older and younger groups were observed for death censored graft survival and in both graft and patient survivals among the elderly with low-risk profiles. 6 In a study comparing the survival rates of recipients older than 65 years to those aged between 60 to 64 or 50 to 59 years, after adjusting for confounders, the authors did not find significant differences for 5-year graft survival by age group.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…[3][4][5] Several studies have reported that graft and patient survivals were lower among patients 60 years or older, when compared with recipients aged 18 to 59. 6,7 On the other hand, similar results between older and younger groups were observed for death censored graft survival and in both graft and patient survivals among the elderly with low-risk profiles. 6 In a study comparing the survival rates of recipients older than 65 years to those aged between 60 to 64 or 50 to 59 years, after adjusting for confounders, the authors did not find significant differences for 5-year graft survival by age group.…”
Section: Discussionsupporting
confidence: 73%
“…6,7 On the other hand, similar results between older and younger groups were observed for death censored graft survival and in both graft and patient survivals among the elderly with low-risk profiles. 6 In a study comparing the survival rates of recipients older than 65 years to those aged between 60 to 64 or 50 to 59 years, after adjusting for confounders, the authors did not find significant differences for 5-year graft survival by age group. 8 Other investigators found similar 5-year graft survivals between the oldest patients (Ͼ60 years) and the youngest group (20 -29 years).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Meier-Kriesche reports a 1-year survival of 81% from their single-center series of patients older than 60 years (8), and Palomar and Doyle report comparable figures for this age group with 78% and 86%, respectively (9). For patients of 65 years and greater with donors older than 65 years, Smits reports a 1-year graft survival of 79% (6).…”
Section: Discussionmentioning
confidence: 93%
“…Wolfe et al [29] compared the survival of primary deceased donor transplant recipients with other dialysis patients and found that among renal transplant recipients patients aged 60-74 years, the cumulative survival rate improved after the first year post-transplantation. More recent studies indicate that in elderly ESRD patients, survival at 1, 5, and 10 years is approximately 80% to 90%, 70%, and 50% respectively [38][39][40][41][42][43][44][45][46]. In the United States there are currently over 16,000 ESRD patients older than 65 years waiting for a kidney transplantation, representing 18% of all listed candidates [1].…”
mentioning
confidence: 99%